Two new species of Anthurium sect. Urospadix (Araceae) endemic to the restinga vegetation of Bahia, Brazil - Pimenta, Karena M.; C. Marinho, Lucas; M. Amorim, André; Mayo, Simon (Phytotaxa, 2024)
Coastal vegetation will be the first areas to be directly affected by rising sea levels as a result of climate change. Thus, it is urgent to know and disseminate information about their plant diversity, especially those that are already known to be impacted by other threat factors. Here we present two new critically endangered Anthurium sect. Urospadix species from the restingas of Bahia, Brazil: A. bellissimum and A. itacarense. Descriptions, illustrations, photos in vivo, as well as discussion on the conservation status and related species are provided.